Video Scribe Media Development Management In Improving Arabic Speaking Skills - Mukhibat, M; Bukhori, Evi Muzaiyidah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
One of the relevant learning media today to improve Arabic speaking skills is audio-visual media in Video scribe. The development of video scribe media is very urgent to do. Because the characteristics of video scribe-based learning can help students to understand and improve Arabic speaking skills by presenting images, sounds, animations, and designed learning materials interestingly to achieve the expected learning objectives, this research, and development (RD) at Kiai Haji Achmad Siddiq State Islamic University (UIN KHAS) Jember has provided a solution to the lack of Arabic learning media. Based on the test results of the validator (media, material, and design experts) on the development of the video scribe media, the score from the validator was based on the value component, namely the score from the learning media expert was 90% with a very valid/decent category, from the Arabic learning material expert got a score of 92 % with very valid/decent category. Moreover, the score from the design expert is 92% in the very valid/decent category. The field trial results using students’ response questionnaire instrument denoted that video scribe media for Arabic speaking skills learning, in general, achieved 47.1%, which indicates that video scribe is an exciting media to use in learning Arabic speaking skills. Besides, the lecturer responded during implementing video scribe media that it was a suitable medium for the pandemic. Thus, it became a solution in learning Arabic speaking skills. Based on these data, the video scribe media developed is feasible to learn Arabic speaking skills.